Assessment of the impact of temporomandibular disorders on maximum bite force - Todic, Jelena; Martinovic, Brankica; Pavlovic, Jasna; Tabakovic, Sasa; Staletovic, Milos (Biomedical papers, 2019)
Aim: Temporomandibular disorders (TMD) refer to functional disorders of the masticatory system, temporomandibular joint (TMJ) and masticatory muscles. The main objective of this study was to determine whether and to what extent temporomandibular disorders (TMD) affect the maximum bite force (MBF). Methods: The present study included subjects with and without temporomandibular disorder. The presence of TMD was assessed by means of the Helkimo clinical dysfunction index analysis. We measured the maximum bite pressure (MBP) and occlusal contact area (OCA) by means of a Fuji Prescale Pressure measurement film. Based on the MBP and OCA values obtained, MBF values were determined. Results: The MBF values were significantly lower in patients with TMD compared to subjects without TMD (P Conclusion: TMDs have a significant impact on MBF and masticatory muscle action potential. More research is needed to determine the impact of reduced maximum bite force on the functional efficiency of the masticatory system.
Keywords: temporomandibular disorders; maximum bite force; occlusal contact area; maximum bite pressure; pressure-sensitive film